Pets and the city : true tales of a Manhattan house call veterinarian - Attas, Amy (G.P. Putnam's Sons, 2024)
"When a pet is sick, people-even the rich and famous-are at their most authentic and vulnerable. They could have a Monet on the wall and an Oscar on the shelf, but if their cat gets a cold, all they want to talk about are snotty noses and sneezing fits. That's when they call premier in-home veterinarian Dr. Amy Attas. In Pets and the City, Dr. Amy shares all the shocking, heartbreaking, and life-affirming experiences she's faced throughout her thirty-year career treating the cats and dogs of New Yorkers from Park Avenue to the projects. Some of her stories are about celebs, like the time she saw a famous singer naked (no, her rash was not the same as her puppy's). Others are about remarkable animals, like the skilled service dog who, after his exam was finished, left the room and returned with a checkbook in his mouth. Every tale in this rollicking, informative, and fun memoir affirms a key truth about animal, and human, nature: Our pets love us because their hearts are pure; we love them because they're freaking adorable. On some level, we know that by caring for them, we are the best version of ourselves. In short: Our pets make us better people"--